A diagnostic model framework for water use in rice-based irrigation systems - Hundertmark, Wilfried; Abdourahmane, A.T. (International Water Management Institute, 2003)
The paper presents a framework for water use in rice-based irrigation systems, which is based on linear programming (LP). This framework intends to facilitate improved understanding of a system's internal and external conditions and the constraints to productive use of the available land and water resources, and thereby create a reference for the assessment of the physical, economic and environmental performance of a given system. The framework is conceived as a tool that is used interactively in technical group sessions with farmers, system operators and extension workers, where structured discussions lead to improved data confidence, and understanding of complex irrigation systems.